EFFECT OF COMBINATION OF BREAST CARE AND OXYTOCIN MASSAGE ON BREAST MILK SECRETION IN POSTPARTUM MOTHERS - Kadek Yuli Hesti; Noor Pramono; Sri Wahyuni; Melyana Nurul Widyawati; Bedjo Santoso (Belitung Raya Foundation, Indonesia, 2017)
Background: Optimal nutrition from an early age can be achieved through exclusive breastfeeding. Lack of milk production is one reason why mothers decide to give formula milk to their babies. In fact, 60% of mothers were unable to breastfeed optimally, thus, breast care and oxytocin massage are proposed to increase milk secretion in postpartum mothers. Objective: To examine the effect of combination of breast care and oxytocin massage on breast milk secretion in postpartum mothers. Methods: This was a quasi-experimental study with non-randomized control trial with pretest-posttest control group, conducted in the working area of the Community Health Center of Batealit of Jepara Indonesia from December 5, 2016 to January 15, 2017. There were 44 postpartum mothers recruited in this study using purposive sampling, which 22 assigned in the experiment and control group. Data were analyzed using dependent t-test and Mann Whitney test. Results: There was a significant increase of breast milk secretion in the experiment and control group with p-value 0.000 (<0.05). In the experiment group, there was an increase of breast milk secretion from 17.09 to 220.91 cc, and in the control group there was also an increase from 17.09 to 72.00 cc. The mean difference of breast milk secretion between pretest and posttest in the experiment group was 203.82 and in the control group was 54.90 with p-value 0.000 (<0.05) Conclusion: There was a significant increase of breast milk secretion in postpartum mothers after given the combination of oxytocin massage and breast care in the experiment group compared with the education and counseling about breast care in the control group. Thus, this result can be used as an evidence to perform oxytocin massage and breast care to increase the secretion of breast milk in postpartum mothers.